Case Report: Infectious prophylaxis in hematological malignancies - Passucci, Mauro; Masucci, Chiara; Paoletti, Francesca; Ielo, Claudia; Costa, Alessandro; Carmosino, Ida; Scalzulli, Emilia; Martelli, Maurizio; Gentile, Giuseppe; Breccia, Massimo (Frontiers in Oncology, 2023)
Patients with hematological malignancies and past serological evidence of hepatitis B are at risk for HBV reactivation. In myeloproliferative neoplasms, continuous treatment with the JAK 1/2 inhibitor ruxolitinib confers a moderate risk of reactivation (1-10%); nevertheless, no prospective randomized data are available to strongly recommend HBV prophylaxis in these patients. Here, we report on a case of primary myelofibrosis and past serological evidence of HBV infection, treated with ruxolitinib and concomitant lamivudine, developing HBV reactivation due to premature withdrawal of prophylaxis. This case underlines the potential need for persistent HBV prophylaxis in the setting of ruxolitinib treatment.